Choosing the carrot or the stick? Endogenous institutional choice in social dilemma situations - Matthias Sutter; Stefan Haigner; Martin G. Kocher (University of Innsbruck, Department of Public Finance, 2008)
We analyze an experimental public goods game in which group members can endogenously determine whether they want to supplement a standard voluntary contribution mechanism with the possibility of rewarding or punishing other group members. We find a large and positive effect of endogenous institutional choice on the level of cooperation in comparison to exogenously implemented institutions. This suggests that participation rights enhance cooperation in groups. With endogenous choice, groups typically vote for the reward option, even though punishment is actually more effective in sustaining high levels of cooperation. Our results are evaluated against the predictions of social preference models.
Keywords: C72; C91; C92; 330; public goods; punishment; reward; endogenous institutional choice; voting; experiment; Kollektives Handeln; Spieltheorie; Öffentliches Gut; Kooperation; Gruppenentscheidung; Partizipation; Test